Fluid and Electrolyte Management in the Neonate: Potassium and Phosphorus - Moss, Colleen Reilly (Neonatal network, 2022)
Maintenance of electrolyte balance in the neonate is challenging in the context of illness or prematurity. Imbalances in potassium and phosphorus can occur in neonates, ranging from benign and clinically insignificant to those that can be life-threatening. An individualized approach to fluid and electrolyte management is based on the neonate's gestational age, day of life, maintenance needs, deficits, and ongoing losses. This article reviews normal and abnormal potassium and phosphorus values along with management strategies. Using a case scenario, the reader can apply concepts outlined in this article to management of critically ill neonates with electrolyte disturbances.Maintenance of electrolyte balance in the neonate is challenging in the context of illness or prematurity. Imbalances in potassium and phosphorus can occur in neonates, ranging from benign and clinically insignificant to those that can be life-threatening. An individualized approach to fluid and electrolyte management is based on the neonate's gestational age, day of life, maintenance needs, deficits, and ongoing losses. This article reviews normal and abnormal potassium and phosphorus values along with management strategies. Using a case scenario, the reader can apply concepts outlined in this article to management of critically ill neonates with electrolyte disturbances.